Needs Analysis of Developing Interactive Electronic Worksheets for Students Integrated by STEM in Senior High School 15 Kerinci - Menza Hendri; Dian Pertiwi Rasmi; Amril Sastra (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2022)
This research aims to analyze the need for the availability of physics teaching materials in the form of electronic worksheets for students which can support the process of teaching and learning activities in senior high school. The demands and needs in fulfilling 21st-century skills need to be considered through the provision of interactive e-worksheets that integrate STEM. This research is qualitative descriptive research using interview techniques consisting of 13 items of questions related to the needs of teaching materials in senior high schools. The results of the interviews were analyzed to determine the need for Electronic Worksheets. The results of the interview analysis showed that the learning carried out today is often online and blended learning. So it is necessary to use teaching materials in the form of interactive e-worksheets during the process of teaching and learning activities with 21st-century learning adjustments. For this reason, it is necessary to develop physics teaching materials in the form of STEM integrated interactive e-worksheets to support meeting the needs of teaching materials by teachers, as well as the needs of students at the SMA 13 Kerinci, in order to be able to learn actively and independently.